The Onomastics of Chocolate and Luxury Sweets. A Sociolinguistic Approach - Ungureanu, Cristina (Journal of Social Sciences and Humanities, 2025)
The relationship between language and branding, deeply embedded in various cultures, has been widely explored in marketing and sociolinguistics, yet the role of onomastics in luxury chocolate branding remains underexamined. Historically, chocolate was associated with prestige and exclusivity, first as a sacred offering among the Aztecs, later as a luxury commodity in 17th-century European chocolate houses. Over time, branding has leveraged onomastics to reinforce chocolate’s elite status, with names inspired by mythology, aristocracy, emotions, and geography, crafting an aura of sophistication. This study investigates how brand names in the chocolate and confectionery industry employ linguistic strategies to evoke exclusivity and sensory appeal. By integrating phonetic elegance, morphological sophistication, and cultural symbolism, luxury chocolate brands craft names that reinforce their prestige and desirability. The study draws on sociolinguistic theories of prestige and branding, analyzing a corpus of one hundred chocolate brand names to uncover phonetic, morphological, and semantic trends that contribute to their market positioning. Findings indicate that phonetic smoothness, diminutive suffixes, and references to aristocratic and geographical origins enhance a brand’s elite image. The prevalence of French and Italian-derived names suggests a deliberate association with culinary excellence and historical luxury. Furthermore, the study explores the semiotic power of chocolate branding, where names act as linguistic markers of indulgence and status. The research contributes to the growing field of commercial onomastics, providing insights into how language influences consumer perception and purchasing behaviour in luxury markets. Future research could examine cross-cultural variations in chocolate branding and the psychological effects of phonetic and morphological choices on consumer engagement. By decoding the linguistic patterns behind successful luxury chocolate brands, this study underscores the intricate relationship between language, branding, and consumer psychology